Strategi Program Jebol Anduk Sebagai Inovasi Pelayanan Administrasi Kependudukan Di Balai RW Kelurahan Gayungan Kota Surabaya - Elisa Dwi Rahmawati; Muhammad Roisul Basyar (Politeknik Kampar, 2023)
Population Administration is an important part of the government system that manages data and information regarding population from birth to death. In accordance with the implementation of Perwali Number 93 of 2023 concerning Amendments to Surabaya Mayor Regulation Number 10 of 2022 concerning Procedures for Implementing Population Administration. Efficient population management is the core of quality public services and has an impact on various aspects of people's lives. However, in reality classic challenges such as complicated bureaucracy and difficult access often become obstacles for people in managing population administration. With the importance of providing administrative services that are more efficient and responsive to community needs, the Surabaya City Government has innovated the Jebol Anduk Program (Pick Up Adminduk Ball). In this approach, sub-district officers and writers actively visit the community at the RW Hall. The goal is to increase efficiency and reduce waiting times and complicated bureaucratic procedures. Apart from that, it can increase accessibility which makes it easier for people to access and manage population administration without having to come to the Subdistrict Office or Dispendukcapil Office. Thus, the Jebol Anduk Program at the Gayungan Subdistrict RW Hall is a positive step towards increasing the efficiency of population administration services and can be an example for other subdistricts in similar efforts.